THE EFFECT OF PRODUCT QUALITY, SERVICE AND TARIFFS ON BILL PAYMENT COMPLIANCE THROUGH CUSTOMER SATISFACTION LEVEL IN THE HOUSEHOLD CATEGORY AT PT AIR BATAM HILIR - Gana Vige Ortega; Ngaliman; Sri Yanti (CV. Radja Publika, 2025)
This study examines the effect of product quality, service, and tariff on bill payment compliance among household customers using customer satisfaction as an intervening variable. The sample in this study was 100 household customers, with data collection using a questionnaire instrument with a Likert scale. The analysis was conducted using Partial Least Square (PLS) with Structural Equation Model (SEM) modeling to test direct and indirect effects. The results of the study indicate that product quality, service, and tariff each have a significant positive effect on payment compliance and customer satisfaction. The results also prove that product quality, service, and tariff have a significant positive effect on bill payment compliance through customer satisfaction. Based on this study, it is known that bill payment compliance can increase when customers are satisfied with the quality of products, services, and tariffs. On the other hand, it is known that to increase payment compliance, it can be achieved by improving the quality of products, services, and current tariffs. This increase will have an impact on increasing customer satisfaction, indicating the fact that customers will feel satisfied and this satisfaction is conveyed by customers in the form of loyalty if there are dimensions of product quality, service, and tariffs in it.